Case History: Antiplatelet Therapy in the Management of STEMI Treated with PCI - Vinall, Maria (MD Conference Express, 2014)
Management of antiplatelet therapy in the treatment of patients with ST segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI) has many decision points. This article described the decisions made to treat a 44-year-old man who presented with severe substernal chest pain (Canadian Cardiovascular Society class IV angina).